Design Expert System to Identify Student Talent Based on Personality Type Using Certainty Factor Method in SMP Muhammadiyah Kandis Siak Riau Province - Febryanto Febryanto; Liza Efriyanti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The goal of this research is to create a system design that